台灣國民小學教師翻轉教學之研究-TALIS 的分析與驗證 Current Situation of Teachers' Flipped Teaching in Taiwan's Elementary Schools - Analysis and Verification of TALIS - 謝傳崇 Chuan-Chung Hsieh; 李孟雪 Meng-Hsueh Lee (National Changhua University of Education, 2021)
翻轉教學的實施，賦予課程改革與創新正面性的意義。而教學與學習國際調查 (TALIS) 是針對學校學習環境與教師工作情況的國際性調查，以教師與校長提供的資訊，做為政策發展的依據。本研究首先探討翻轉教學之意涵，並參照 TALIS-2018 調查數據，再以訪談個案方式輔以證明，分析臺灣國小教師翻轉教學的實施現況並提出建議，以作為實施翻轉教學之參考。研究結論包括：學習環境與學生常規、秩序之建立息息相關；學生自主能力與教師態度，影響學習文化；資訊科技之使用難易，影響教師規劃學習內容之心態；在翻轉教學領域，教師是專業的教育工作者。本研究之建議如下：訂定班級經營策略，透過獎勵讓時間更具彈性，以營造靈活的學習環境；重視與強化學生自主能力之培養，建立豐富的學習文化；簡化資訊科技使用步驟，積極解決教師使用之困境，讓教與學更有意義；提升教師進行質性回饋的專業度，讓教師成為更專業的教育工作者。 The implementation of flipped teaching offers the meaning of positive curriculum reform and innovation. The International Survey of Teaching and Learning (TALIS) is a global survey of schools' learning environment and the work of teachers. The information provided by teachers and principals serves as the basis for policy development. This research thus discusses the meaning of flipped teaching and analyzes the implementation status of Taiwan's elementary school teachers' flipped teaching through the TALIS-2018 survey data, supplemented by an interview case, and makes recommendations as a reference for implementing flip teaching. The conclusions include the following: 1) student routines and order closely relate to the establishment of the learning environment; 2) student autonomy and teacher attitudes affect learning culture; 3) the difficulty of using information technology affects teachers' mentality of planning learning content; and 4) in the field of flipped teaching, teachers are professional educators. The recommendations are as follow: 1) set up a class management strategy, make time more flexible through rewards and create a flexible learning environment; 2) value and strengthen students' self-learning ability to establish a rich learning culture; 3) simplify the use of information technology, actively solve the dilemma of teachers' use of flipped teaching and make the learning content more meaningful; 4) enhance the professionalism of teachers to give quality feedback and help the teachers to become more professional educators.